It's a Match? the Influence of Goal Matching in Couple Therapy. Issue 2 (2nd April 2020) - Smith, Amy D.; Quirk, Kelley; Pinsof, William; Goldstein, Jacob
Abstract: The degree which partners have aligned goals for therapy is an important, understudied psychotherapy predictor. Growth models were performed to examine group differences in alliance and outcome variables. Results revealed couples reported significantly lower commitment and sexual satisfaction in the mismatched group at the intercept but no significant trajectory differences. The matching group reported higher individual- and between-partner alliances initially but as sessions progressed, the mismatch group displayed significantly higher within-alliance ratings. This suggests couples with matched versus mismatched goals start therapy in different places and therapists may play an important role helping couples become more aligned as therapy progresses.